Implementation of Rapid Application Development (RAD) for Community-based Ecotourism Monitoring System - Singgalen, Yerik Afrianto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
One of the challenges of tourism development in North Halmahera Regency is integrating technology in decision-making to determine leading and priority tourist destinations. Thematically, the ecology-based tourism development approach is the concept of ecotourism that balances environmental sustainability with tourism economic growth; however, tourism databases and information systems need to be developed by considering economic, socio-cultural, and environmental distribution and growth. This research adopts the Rapid Application Development (RAD) method in designing the Community-based Ecotourism Monitoring System. The stages in the RAD method consist of requirements planning, user interface design, construction, and cutover stages. At the requirement planning stage, this system will accommodate three main aspects: local attraction, local transportation, and local accommodation. A local attraction focuses on ecotourism development approaches, while local transportation refers to local transportation services managed individually or community-based. In addition, local accommodation refers to the business of homestay accommodation services as a form of community participation in tourism activities. At the construction stage, the instrument used in designing this system database is oracle-apex, which utilizes map, classic report, and form (modal dialog) features. Features and functions are tested at the cutover stage, and access rights restrictions are provided based on administrator, user, and viewer roles. The system design results show that policymakers must support community involvement in each tourist destination in determining priority areas for ecotourism infrastructure development. The testing result shows that all the features and operators are thriving and ready to be used. Thus, implementing RAD in the design of a community-based ecotourism monitoring system can be adapted to the context of ecotourism in North Halmahera Regency, North Maluku Province, Indonesia.